2021
DOI: 10.1371/journal.ppat.1009213
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring substitution in one amino acid in VHSV phosphoprotein enhances viral virulence in flounder

Abstract: Viral hemorrhagic septicemia virus (VHSV) is a rhabdovirus that causes high mortality in cultured flounder. Naturally occurring VHSV strains vary greatly in virulence. Until now, little has been known about genetic alterations that affect the virulence of VHSV in flounder. We recently reported the full-genome sequences of 18 VHSV strains. In this study, we determined the virulence of these 18 VHSV strains in flounder and then the assessed relationships between differences in the amino acid sequences of the 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…There are reports in the literature on viral adaptation to new hosts or conditions led by changes in protein function: one recent example is the adaptation to thermal stresses of a polerovirus driven by a single amino acid substitution in its suppressor of silencing that increases its stability and its silencing suppression strength at high temperatures (Cai et al., 2023). In the case of the genus Potyvirus , examples of adaptation have been documented and associated with mutations in certain cistrons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports in the literature on viral adaptation to new hosts or conditions led by changes in protein function: one recent example is the adaptation to thermal stresses of a polerovirus driven by a single amino acid substitution in its suppressor of silencing that increases its stability and its silencing suppression strength at high temperatures (Cai et al., 2023). In the case of the genus Potyvirus , examples of adaptation have been documented and associated with mutations in certain cistrons.…”
Section: Introductionmentioning
confidence: 99%
“…Ambient alterations affect host plants in their physiology (i.e., within-plant transport, intracellular conditions, molecular pathways including defence responses). Abiotic environment parameters such as, for example, ambient temperature, CO 2 partial pressures (Aguilar et al, 2015;Cai et al, 2023;Choi et al, 2017;Chung et al, 2017;del Toro et al, 2015del Toro et al, , 2018 and water deprivation (Aguilar et al, 2017;Gutiérrez-Sánchez et al, 2023) have been shown to alter the dynamics of infection. Biotic environment parameters also influence infections (i.e., exposure to, or co-infection with other viruses [Aguilar et al, 2015], or with other agents like bacteria or fungi).…”
mentioning
confidence: 99%
“…suggested that this cofactor is present in the P protein and could be a specific amino acid signature. Recently,Hwang et al (2021) have reported that a single substitution in the P protein of VHSV genotype IVa has enhanced virulence in olive flounder. The comparison of translated P gene of rVHSV SE 9C and DK-3592B showed only four disagreements(positions 23, 39, 41 and 210).…”
mentioning
confidence: 99%